2020
DOI: 10.1108/jpbm-08-2019-2543
|View full text |Cite
|
Sign up to set email alerts
|

Beyond lurking and posting: segmenting the members of a brand community on the basis of engagement, attitudes and identification

Abstract: Purpose Brand communities are an increasingly important way for brands to interact with their customers, as they give brands an opportunity to learn from and interact with people with a demonstrated interest in the brand. Literature has explored the difference between lurkers and posters within these brand communities. However, there are other ways to segment members, just as there are many ways to segment customers of products and services – and this paper aims to be a step toward going beyond simple lurking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 86 publications
(114 reference statements)
1
18
0
Order By: Relevance
“…Studies, however, show that people who are more willing to consume informative content on social media are more likely to develop favorable attitudes toward the brand (Qin, 2020). Enriching and stimulating content can affect the identification of the members who feel that the content they see reflects their interests, values they stand for and also elevates their social status (Madupu and Cooley, 2010;Haverila et al, 2020). Fernandes and Castro also reported that information need is the strongest predictor of lurking behavior on Facebook (2020).…”
Section: Augmenting Brand Communitymentioning
confidence: 99%
“…Studies, however, show that people who are more willing to consume informative content on social media are more likely to develop favorable attitudes toward the brand (Qin, 2020). Enriching and stimulating content can affect the identification of the members who feel that the content they see reflects their interests, values they stand for and also elevates their social status (Madupu and Cooley, 2010;Haverila et al, 2020). Fernandes and Castro also reported that information need is the strongest predictor of lurking behavior on Facebook (2020).…”
Section: Augmenting Brand Communitymentioning
confidence: 99%
“…Researchers note the need to account for unobserved heterogeneity and group-specific differences in research (Becker et al, 2013;Sarstedt et al, 2017). Treating all individuals alike ignores the individual differences in needs and motivations leading to lower engagement with the organisation with adverse consequences such as leaving the organisation or spreading negative word-of-mouth (Haverila et al, 2020). Moreover, ignoring the presence of unobserved heterogeneity may lead to incorrect estimation of parameters (Becker et al, 2013;Marques and Reis, 2015) and produce results, which are biased and conclusions, which may be false and misleading (Hair et al, 2019b).…”
Section: Resident Heterogeneitymentioning
confidence: 99%
“…Moreover, ignoring the presence of unobserved heterogeneity may lead to incorrect estimation of parameters (Becker et al, 2013;Marques and Reis, 2015) and produce results, which are biased and conclusions, which may be false and misleading (Hair et al, 2019b). Recent research studies have highlighted the importance of uncovering unobserved heterogeneity in different contexts such as brand community (Haverila et al, 2020), information systems (Becker et al, 2013), internet search engines (Palos-Sanchez et al, 2018), internet users (Arenas-Gait an et al, 2019), retail banking (Kamath et al, 2019) and tourism (Marques and Reis, 2015;Zhang et al, 2019). Although prior studies argue that it is important to identify resident segments because each segment is motivated by different needs and desires (Freire, 2009), limited research has gone into identifying the unobserved heterogeneity amongst residents.…”
Section: Resident Heterogeneitymentioning
confidence: 99%
“…In fact, consumers not only build connections with brands but also with fellow brand enthusiasts (Badrinarayanan and Sierra, 2018;Hughes et al, 2016). They engage with the brand, share information and express their views on the brand (Fetscherin et al, 2021;Wallace et al, 2017) and embrace a shared culture, rituals, and traditions with a collective identity (Haverila et al, 2020). These consumers strive to maintain an image others (i.e., brand enthusiasts) have of them (i.e., social self) in order to facilitate social interactions and approval (Swann et al, 1992).…”
Section: Introductionmentioning
confidence: 99%